Medical Innovations and Ageing: A Health Economics Perspective - Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper discusses the relationship between medical innovations and ageing from a health economics perspective and surveys empirical evidence on medical R&D incentives, R&D costs of pharmaceuticals, and the cost-effectiveness of health innovations. Particular focus is on the endogeneity of medical technological progress to expected market size and on the conceptualization of ageing as an accumulation of health deficits. The paper also discusses the role of medical progress for longevity and health inequality and presents a framework to assess the effect of increased longevity on the value of life.
Keywords: I10; O30; 330; healthcare; health deficits; health innovations; medical technological progress; longevity